Hubungan pengetahuan gizi ibu dengan kecukupan asupan energi anak usia 1-3 tahun di Desa Mopusi Kecamatan Lolayan Kabupaten Bolaang Mongondow Sulawesi Utara - Watania, Tasya; Mayulu, Nelly; Kawengian, Shirley E.S. (e-Biomedik, 2016)
Abstract: Nutritional adequacy or sufficiency of energy in infants is still a public health problem, especially in developing countries and poor countries. As a developing country, Indonesia still has macronutrient deficiencies such as stunting, wasting, and underweight. Maternal level of knowledge about nutrition influences the attitude and behavior in chosing the appropriate and qualified food. This study was aimed to determine the relationship between maternal knowledge and the adequacy of energy intake of toddlers at Mopusi village. This was a correlation study with a cross sectional design. Respondents of this study were mothers who had toddlers aged 1-3 years and lived at Mopusi vollage in September 2014 - December 2014. Data were analyzed by using SPSS. The results showed that there were 90 mothers as respondents. Based on maternal knowledge about nutrition, there were 41 respondents (45.6%) with poor knowledge. Based on adequate intake of energy toddlers, there were 75 toddlers (83%) with less energy intake. The relationship between maternal knowledge about nutrition and the adequacy of energy intake among toddlers showed the correlation coefficient r = 0.06 and p = 0.97. Conclusion: There was no significant correlation between maternal knowledge about nutrition and the adequacy of energy intake among toddlers at Mopusi village. Keywords: mother’s knowledge about nutritions, energy intake, toddlers Abstrak: Kecukupan gizi atau kecukupan energi pada balita masih menjadi masalah kesehatan masyarakat terutama dinegara-negara berkembang dan negara miskin. Sebagai negara berkembang, Indonesia mempunyai masalah defisiensi makronutrien antara lain stunting, wasting dan underweight. Tingkat pengetahuan gizi seseorang ibu berpengaruh terhadap sikap dan perilaku dalam pemilihan makanan. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan ibu dengan kecukupan asupan energi batita di Desa Mopusi Kecamatan Lolayan Kabupaten Bolaang Mongondow Induk. Jenis penelitian ialah korelasi dengan desain potong lintang. Responden penelitian ialah ibu yang memiliki batita usia 1-3 tahun dan berdomisili di Desa Mopusi pada bulan September 2014 – Desember 2014. Data dianalisis menggunakan SPSS. Hasil penelitian mendapatkan sebanyak 41 responden (45,6%) berpengetahuan gizi kurang. Mengenai kecukupan asupan energi dari 90 sampel penelitian terdapat 75 batita (83%) dengan asupan energi kurang. Hubungan pengetahuan gizi ibu dengan kecukupan asupan energi batita mendapatkan koefisien korelasi r= 0,06 dan p= 0,97. Simpulan: Tidak terdapat hubungan bermakna antara pengetahuan gizi ibu dengan kecukupan asupan energi batita di Desa Mopusi.Kata kunci: pengetahuan gizi ibu, asupan energi, batita.